DOES OPTION THEORY HOLD FOR MAJOR LEAGUE BASEBALL CONTRACTS?. (19th May 2016) - Gross, Alexander; Link, Charles
Abstract : We test whether option theory indicated by the Black–Scholes formula is consistent with contract negotiations between teams and players in Major League Baseball (MLB). Teams use contract options in order to obtain the right to buy a player's services for an extra year when negotiating multiple year contracts. These options are similar to European call options, and should reduce the risk of buying volatile assets (players with high variation in performance). In this paper, we model the decision to buy an option (include an option year in the contract) and whether to exercise the option (pay the option salary in the option year versus buying out the option). The results indicate that the behavior of MLB teams is consistent with standard option theory both in terms of buying and exercising options. The sample is the complete population of free agent hitters who signed new contracts between the years 2003 and 2011. We were unable to find any published literature that has addressed this issue. ( JEL ZO, H3)